Echoes in the body : understanding deaf embodiment - Karjalainen, Noora (Taideyliopiston Teatterikorkeakoulu, 2022)
In this thesis, I consider the corporeality of a deaf person in the context of theatre pedagogy. I approach the subject through the framework of embodied learning and holistic conception of human beings, looking for answers to questions such as how deaf bodies are in this world, and how deaf bodies think. With these questions, I seek to find new practices in my own artistic and pedagogical practice that I can use to develop deaf-based learning environments and performative spaces. These pedagogical and performative spaces are not based on the laws of the theatrical tradition of the hearing people, such as sound and speech, but seek to free the deaf from a constant cycle of adaptation and reasonable adjustments towards selfdetermined corporeality, theatre, and aesthetics. My thesis work was divided into two parts: it includes an empirical data collection part and a written study part. In the practical part of the thesis, I conducted a total of four days of art pedagogical laboratory at the Theatre Academy and yoga studio Joogaholiaa, where we studied embodiment and corporeality with five other deaf signers. I approached the laboratory work in such a way that instead of asking precise questions, I let the work to proceed according to the interests of both the group and myself, and I observed what this laboratory brought to the surface. The research method thus became echoes in the body, in which my own position as an art pedagogue-researcher was determined through continuous cycle of presence, listening, and reflection. In the written part of the thesis, I present the findings made during the laboratory and reflect on the deaf embodiment in the light of my personal experiences and observations. I discuss, among other things, the embodied trauma experienced by the deaf, the contradictions between the deaf and the hearing lifeworlds that have occurred in different teaching situations, and aside of verbal or signed input what else can an instruction be. This thesis aims to participate in art pedagogical and norm-critical discussions about, among other things, the role of art pedagogy and the representation in performing arts. In support of my reflection, I use the central ideas of Paulo Freire’s critical pedagogy and bell hooks’ engaged pedagogy. The aim of this thesis is not to produce or present generalizable information about the embodiment of the deaf, but its perspective is experiential and reflective.
Keywords: Embodiment; Corporeality; Multicensory experience; Multimodality; Experiential knowledge; Perception; Theatre; Pedagogy; Deafness; Critical thinking; Critical pedagogy; ruumis; ruumiillisuus; ruumiinkuva; aistimukset; käsitykset; teatteritaide; pedagogiikka; kuurous; moniaistisuus; multimodaalisuus; kokemustieto; kriittinen ajattelu; kriittinen pedagogiikka; kroppen; kroppsuppfattning; kroppslighet; sinnesförnimmelser; uppfattningar; teaterkonst; pedagogik (undervisning); dövhet; multisensorisk upplevelse; multimodalitet; empirisk kunskap; kritisk pedagogik; havaitseminen; fi=teatteriopettaja|sv=teaterpedagogik|en=Theatre Pedagogy|